YEARLY VARIATION IN CERTAIN PHYSICO-CHEMICAL PARAMETERS OF POND AT EASTERN DOON VALLEY - VS, J.; ., RAUTHAN; BISHT, SHASHI; GROVER, S.P (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Samples of water of the pond at Eastern Doon Valley were analysed for water and atmospheric temperature, pH value, dissolved oxygen, free carbondioxide, alkalinity, phosphates, nitrates, total dissolved solids (TDS), and total suspended solids (TSS).